New records of spongicolid shrimps (Crustacea, Decapoda, Stenopodidea) from Taiwan - Chen, Chien-Lin; Chan, Tin-Yam (Zootaxa, 2022)
Spongicolid shrimps of the three genera, Engystenopus Alcock & Anderson, 1894, Spongicola De Haan, 1844 and Spongicoloides Hansen, 1908 are recorded from Taiwan for the first time. The newly recorded species are Engystenopus palmipes Alcock & Anderson, 1894, Spongicola andamanicus Alcock, 1901, S. goyi Saito & Komai, 2008, S. levigatus Hayashi & Ogawa, 1987 and Spongicoloides iheyaensis Saito, Tsuchida & Yamamoto, 2006. A total of six genera and nine species of stenopodidean shrimps are now known from Taiwan. A key to the Taiwanese species of stenopodideans is provided.